Response of Neoadjuvant Chemotherapy in Triple Negative Breast Cancer and the Impact of Pathologic Complete Response on Survival, an Institutional Research - Hanif, Muhammad Rashid; Wahab, Abdul; Moeed, Amna; Khan, Shafquat Ali; Sheikh, Rizwan Masood; Siddiqui, Neelam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate response of neoadjuvant chemotherapy in Stage I-III triple-negative breast cancer and impact of pathologic complete response on survival. Study Design: Retrospective longitudinal study. Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital & Research Centre, Lahore Pakistan, from Jan 2006 to Jul 2014. Methodology: All patients with triple-negative breast cancer who received neoadjuvant chemotherapy were included and data was retrieved from cancer registry of hospital. The patients received neoadjuvant chemotherapy followed by surgery. Radiotherapy was given wherever clinically indicated. Kaplan-Meier and log-rank test was used to calculate survival. Results: Out of 1113 triple negative breast cancer patients, 150 received neoadjuvant chemotherapy. Mean age was 43±7 years. Fifty-two patients (34.7%) achieved pathological complete response (complete eradication of invasive or in situ carcinoma in breast and axilla (ypT0/is/ypN0) in surgical specimen). Over a median follow up of 61 months, 52 patients (34.7%) had disease progression. Patients with pathological complete response had significantly better 5-years disease-free survival (p-value 0.001) and 5-years overall survival (p-value 0.002) in comparison to non-pathological complete response group. The 5-years disease-free survival was 90% in pathological complete response group compared to 55% in non-pathological complete response group. Similarly, 5-years overall survival was 94% in pathological complete response group compared to 70% non-pathological complete response group. Conclusions: Neoadjuvant chemotherapy is an effective treatment modality in management of triple-negative breast cancer. Achievement of pathological complete response is a potential surrogate endpoint as it is associated with significantly better disease-free survival and overall survival.